2008
DOI: 10.1016/j.ijgo.2008.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for women's health from the Global Burden of Disease study

Abstract: Women's health is increasingly recognized as a global health priority. It is essential to address not only sexual and reproductive health, but also other health issues that occur throughout life. This paper uses the 2005 estimates of morbidity and mortality from the WHO Global Burden of Disease study and a review of the literature to identify key areas of concern for women by age group and world region. The leading causes of death in women aged between 15 and 44 years include infectious diseases such as HIV/AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Women’s nutrition matters not only to women, their children and families, but also to their society, and interventions targeted at improving women’s nutrition should be incorporated into national health strategies without any delay [15]. The interventions should target the most vulnerable age groups.…”
Section: Maternal Undernutritionmentioning
confidence: 99%
“…Women’s nutrition matters not only to women, their children and families, but also to their society, and interventions targeted at improving women’s nutrition should be incorporated into national health strategies without any delay [15]. The interventions should target the most vulnerable age groups.…”
Section: Maternal Undernutritionmentioning
confidence: 99%
“…4 A study of women's health priorities based on the 2004 mortality estimates and disease burden of the WHO Global Burden of Diseases Study found that burns in young women were common in Southeast Asia, with it being the third cause of death for women aged 15-44, followed by self-inflicted injuries. 5 Burn-related injuries and deaths amongst women in India are likely to be caused by: kitchen accidents related to use of kerosene and flammability of garments; self-immolation or suicides; and homicides related to domestic violence. Evidence suggests that domestic violence (physical, sexual and emotional), which is widespread in India, could have an important role in these burn injuries.…”
Section: Introductionmentioning
confidence: 99%
“…It is required that they have physical and mental health (1,2). The world health organization introduced females' health as the growth indices of countries (3).…”
Section: Introductionmentioning
confidence: 99%